Evaluation of the Blood Level of Adiponectin in Pregnant Adolescents - Pádua, Elaine Cristina Rocha; Daher, Silvia; Sampaio, Isa de Pádua Cintra; Araujo Júnior, Edward; Guazzelli, Cristina Falbo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To evaluate serum levels of adiponectin in pregnant adolescents between 30 and 36 weeks of gestation.Method: A prospective cross-sectional study enrolled 67 normal pregnant women between 30 and 36 weeks of gestation and eutrophic (body mass index [BMI]: 18.5–25 kg/m2), of which 36 were adolescents (< 20 years old) and 31 adults (≥ 20 years old). Serum adiponectin levels were determined by enzyme-linked immunosorbent assay (ELISA). The t-student or Mann-Whitney tests were used for intergroup comparison.Results Pregnant adolescents showed significantly higher serum adiponectin concentrations compared with pregnant adults (p = 0.04). No differences were observed in adiponectin levels in younger pregnant adolescents (< 16 years old) compared with older pregnant adolescents (≥ 16 years old). Adiponectin values were divided into 3 subgroups: < 3,000 ng/mL, between 3,000 and 5,000 ng/mL, and > 5,000 ng/mL. Birthweight was significantly higher in women > 5,000 ng/mL when compared with < 3,000 ng/mL in the adolescent group. No association between pregestational adiponectin levels and BMI, gestational weight gain, and gestational age was observed; however, there was a positive relation with birthweight (p = 0.0239).Conclusion Serum adiponectin values in pregnant adolescents between 30 and 36 weeks of gestation were higher compared with pregnant adults; however, no differences between younger and older pregnant adolescents were observed.
Keywords: adiponectin; adolescence; gestation; inflammation